THE EFFECT OF DIGITAL BANKING SERVICES ON CUSTOMER GROWTH - Yusupov Ulug‘bek Mamayusupovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study examines the effect of digital banking services on customer growth  in  the  financial  sector.  In  recent  years,  the  rapid  development  of  financial technologies  has  significantly  transformed  traditional  banking  systems,  making services  more  accessible,  faster,  and  more  efficient.  Digital  banking  tools  such  as mobile banking applications, online payment systems, internet banking platforms, and electronic wallets have become key drivers of customer acquisition and retention.